Performance Analysis of IEEE 802.11 based Long-range Drone Networks in Disaster Environment - Cho, Jun Woo; Lee, Jung Hoon; Baik, Jong Soo; Kim, Jae Hyun (International Conference on ICT Convergence, 2021)
IEEE 802.11 is commonly used for drone networks in a disaster environment. Because it is flexible, allows for high-speed transmission, and is cheaper than a Cellular system. However, it is not suitable for drone networks to maintain a long safe distance due to the limitations of PHY and medium access control (MAC) parameters. This paper identifies the limitation of IEEE 802.11 PHY and MAC parameters and tunes them for long-range drone networks. To do this, we first find the relationship between transmitted power, received power, and 3D distance to use an air-to-ground path loss model. Next, we identify the limitations of existing MAC parameters and adjust them. After that, performance evaluations of average network throughput and delay are performed according to the adjusted PHY and MAC parameters.
Keywords: Cellular system; Control parameters; CSMA-CA; Drone network; High speed transmission; IEEE 802.11; Performances analysis; Pubic safety network; Safe distance; Safety network; CSMA/CA; Drone network; IEEE 802.11; Pubic safety network